2022
DOI: 10.3390/plants11233318
|View full text |Cite
|
Sign up to set email alerts
|

Potentilloside A, a New Flavonol-bis-Glucuronide from the Leaves of Potentilla chinensis, Inhibits TNF-α-Induced ROS Generation and MMP-1 Secretion

Abstract: The major contributor to skin aging is UV radiation, which activates pro-inflammatory cytokines including TNF-α. TNF-α is involved in the acceleration of skin aging via ROS generation and MMP-1 secretion. In our preliminary study, a 30% EtOH extract from the leaves of Potentilla chinensis (LPCE) significantly inhibited TNF-α-induced ROS generation in human dermal fibroblasts (HDFs). Therefore, the objective of this study is to identify the active components in LPCE. A new flavonol-bis-glucuronide (potentillosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Similar to our findings, previous studies have demonstrated that flavonoids derived from natural sources exhibit anti-skin aging activity. For instance, potentilloside A has been shown to inhibit ROS generation and MMP-1 secretion in TNF-α-induced HDFs [70]. Additionally, quercetin, myricetin, and kaempferol have been reported to inhibit expression and superoxide anion radicals in UV-induced human dermal fibroblasts [71].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our findings, previous studies have demonstrated that flavonoids derived from natural sources exhibit anti-skin aging activity. For instance, potentilloside A has been shown to inhibit ROS generation and MMP-1 secretion in TNF-α-induced HDFs [70]. Additionally, quercetin, myricetin, and kaempferol have been reported to inhibit expression and superoxide anion radicals in UV-induced human dermal fibroblasts [71].…”
Section: Discussionmentioning
confidence: 99%
“…Excessive UV irradiation generates ROS, which is a key cellular factor in physiological photoaging [37]. Excessive oxidative stress generated by UVB irradiation induces the activation of the MAPK signaling pathway, followed by that of AP-1 and NF-kappa B.…”
Section: Discussionmentioning
confidence: 99%
“…The leaves of P. chinensis were collected in August at Evada Botanical Garden (GPS coordinates: X: 126.926768 and Y: 37.2482236) and dried for extraction. Four flavonol-diglucuronides (1 and 3-5), five flavonol-mono-glucuronides (2 and 8-11), and two flavonemono-glucuronides (6 and 7) were isolated from the 30% ethanol extract of P. chinensis leaves (Figure 1) [13].…”
Section: Sample Preparationmentioning
confidence: 99%
“…All isolates were tested for the inhibition of TNF-α-induced ROS at each concentration, with no effect on cell proliferation or inhibition, and the isolates showed a significant inhibitory effect. Among the isolates, four flavonol-bis-glucuronides, which are rare in nature and whose pharmacological activity is not well known, were tested for their MMP-1 inhibitory effect, and potentilloside A and quercetin-bis-3,7-O-β-D-glucuronide showed significant inhibition [13]. Thus, the possibility of new activities of the two structurally rare compounds was suggested.…”
Section: Introductionmentioning
confidence: 99%